2023
DOI: 10.1001/jamanetworkopen.2023.45175
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms and Microglial Activation in Patients with Alzheimer Disease

Cristiano Schaffer Aguzzoli,
Pâmela C. L. Ferreira,
Guilherme Povala
et al.

Abstract: ImportanceNeuropsychiatric symptoms are commonly encountered and are highly debilitating in patients with Alzheimer disease. Understanding their underpinnings has implications for identifying biomarkers and treatment for these symptoms.ObjectiveTo evaluate whether glial markers are associated with neuropsychiatric symptoms in individuals across the Alzheimer disease continuum.Design, Setting, and ParticipantsThis cross-sectional study was conducted from January to June 2023, leveraging data from the Translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…These animal models can only partially clarify what happens in humans due to the fact that AD is a proper human disease which is complex and related to both genetic and environmental factors, with a trajectory of evolution that is different and peculiar for each patient. Just think of the association recently demonstrated between imaging markers of microglial reaction and behavioral symptoms in Alzheimer's disease [220], which is certainly not transferable to mouse models. Thus, the role of microglia in human healthy aging and in AD presents multiple aspects, complex and interconnected.…”
Section: Discussionmentioning
confidence: 99%
“…These animal models can only partially clarify what happens in humans due to the fact that AD is a proper human disease which is complex and related to both genetic and environmental factors, with a trajectory of evolution that is different and peculiar for each patient. Just think of the association recently demonstrated between imaging markers of microglial reaction and behavioral symptoms in Alzheimer's disease [220], which is certainly not transferable to mouse models. Thus, the role of microglia in human healthy aging and in AD presents multiple aspects, complex and interconnected.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal neuroinflammation has been linked to the longitudinal worsening of cognitive function among patients with AD [ 54 ]. NPS severity has been correlated with increased microglial activation across the AD continuum [ 55 ]. Excessive neuroinflammatory responses have also been related to anxiety and depressive, manic, and psychotic symptoms in several psychiatric disorders [ 56 ].…”
Section: The Relationship Between Other Alzheimer’s Disease (Ad)-rela...mentioning
confidence: 99%
“…In this context, it has been recently demonstrated that among cognitively unimpaired older individuals, astrocytic PRSs for AD are linked to the beta-amyloid burden, while microglial PRSs for AD are linked to both beta-amyloid and tau accumulation. Given the association between neuroinflammation and NPSs across the AD spectrum, future studies should also investigate the relationship between glial PRSs for AD and MBI [ 55 ].…”
Section: Future Perspectivesmentioning
confidence: 99%